Ethnobotanical Study of Early Childhood Medicinal Plants Used by the Local People in South Bangka Regency, Indonesia - Henri, Henri; Nababan, Vitryany; Hakim, Luchman (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
South Bangka Regency has a long history of using medicinal plants as part of its medical system. However, the potential associated with this aspect of traditional medicine remains understudied and poorly explored. This study aimed to describe the types of medicinal plants and analyze the use of medicinal plants to treat early childhood disease by the local community of South Bangka Regency. The research method used was open interview with local people using the questionnaires. The data was analyzed using Use Value (UV), Fidelity Level (FL), and Relative Frequency of Citation (RFC). The analysis identified 55 plant species from 35 families. The most common families were Euphorbiaceae (8.92%), Fabaceae (7.14%), Poaceae (7.14%), Zingiberaceae (5.36%), and Lamiaceae (5.36%). The most widely used plant was shallot plants (Allium cepa L.) with values of UV, FL, and RFC were 0.67, 66.67, and 0.015, respectively. This study revealed the richness of ethnomedicinal knowledge in the South Bangka Regency. Finally, it is expected that this ethnobotany study can provide a database for further scientific research. The community’s knowledge as a legacy will not be repeated if it is not inherited. Besides, this biodiversity is very important as a socio-economic and ecological asset in South Bangka Regency which must be protected by all means from over exploitation.